Implementasi Kurikulum Merdeka Belajar Kampus Merdeka di Perguruan Tinggi: Implementasi dan Dampaknya Terhadap Pembelajaran Mahasiswa - Suhendra, Suhendra; Suprianto, Bambang (Indo-MathEdu Intellectuals Journal, 2023)
The independent learning of independent campus concept is an innovative effort to provide students with greater flexibility and autonomy in planning and managing their education. This research aims to analyze how the curriculum is implemented in various universities and its impact on student learning experiences. This research method uses a mixed-methods approach. Data collection techniques in this research include surveys, interviews and document analysis at several universities that implement the Merdeka Belajar Kampus Merdeka curriculum. The research results show that the implementation of this curriculum varies between institutions, but generally creates opportunities for students to be more independent in choosing courses, determining learning paths, and combining learning experiences inside and outside the classroom. Observed positive impacts include increased student motivation, better mastery of the material, and more active involvement in the learning process. However, challenges such as the need to support students in planning their curriculum and assessing learning achievement remain a concern. Implementation of the Merdeka Belajar Kampus Merdeka curriculum in tertiary institutions requires continuous attention and adjustments to provide maximum benefits for students